PERAMALAN JUMLAH PRODUKSI BATUBARAMENGGUNAKAN METODE ARIMA (STUDI KASUS: PT ARUTMIN INDONESIA SITE ASAM-ASAM) - Gadys Nauli Simanjuntak; Nur Salam; Maisarah Maisarah (EPSILON: JURNAL MATEMATIKA MURNI DAN TERAPAN, 2023)
In the world of industry and investment, the mining sector has an important role in producing natural resources in Indonesia. South Kalimantan Province is one of the regions which is very famous for being rich in natural resources, especially in the mining sector, especially energy minerals in the form of coal. In recent years, coal production at PT. Arutmin Asam Asam experienced an unstable amount of production. This study aims to obtain the best model and predict the amount of coal production at PT Arutmin Indonesia Site Asam-Asam, South Kalimantan Province using the ARIMA (Autoregressive Integrated Moving Average) method. The best Autoregressive Integrated Moving Average (ARIMA) method for predicting coal production at PT Arutmin Indonesia Site Asam-Asam is the ARIMA model (2,1,3) with a smaller Root Mean Square Error (RMSE) compared to other models, namely 92029.74. Forecasting results of coal production at PT Arutmin Arutmin Site Asam-Asam from January to August 2023 tend not to indicate stability or there will be increases and decreases in the forecasting results obtained.